PELATIHAN BAHASA INGGRIS DAN PUBLIC SPEAKING UNTUK MENINGKATKAN HUMAN CAPITAL DESA SUMBERADI YOGYAKARTA - Restu Arini; Valentina Dyah Arum Sari; Supartini Supartini; Khairunnisa Wijayanti (Jurnal Abdimas Bina Bangsa, 2023)
Human capital is an investment in human resources which will significantly influence the welfare and economic growth of a country. Improving human capital is one of the development targets of Sumberadi Village, Sleman Yogyakarta. Providing education or training becomes the concern to support human resources to be competitive in the world of work is the main objective of this community service. The method applied in this community service is simulated-based technique. This community service offered a training emphasizing on softskills: English and public speaking as an effort to boost the human capital. The method used is simulation-based technique which explores more on practice that is made based on real-life situation. The training involved 25 participants of Sumberadi Village with the range of age between 18-45 years old. The result shows the improvement of the participant’s English skills in basic level and their ability to perform in public. Even, the partcipants request to have an English Club as a medium to contiune practicing their English